Compensation Analysis of Puskesmas Employee Performance in Madiun City - Henrico Roberta Veonardo; Retno Widiarini (Sarana Ilmu Indonesia (salnesia), 2023)
Compensation is a reflection of the organization's efforts to retain employees and a form of appreciation for employee performance. Based on SKP data at one of the community health centers in Madiun City, it is known that employee performance has decreased in 2017 and 2019 and in 2021 PKP data it is known that 5 out of 8 indicators did not reach the target. The aim of this research was to analyze the performance of community health center employees in Madiun City. The research was carried out using a quantitative research approach with a cross sectional approach. Analyzing existing data was carried out using univariate and bivariate with ordinal regression tests. The total sample was 42 employees of one of the community health centers in Madiun City with the Slovin formula d=0,1 using probability sampling with the simple random sampling method. The results of this research show that the sig value of 0,202 > 0,1 means that there is no influence on the performance of community health center employees in Madiun City. Therefore, it is important for community health centers to analyze more deeply other factors that can influence the performance of their employees.